2014
DOI: 10.1093/humrep/deu027
|View full text |Cite
|
Sign up to set email alerts
|

Gamete donors' expectations and experiences of contact with their donor offspring

Abstract: STUDY QUESTIONWhat are the expectations and experiences of anonymous gamete donors about contact with their donor offspring?SUMMARY ANSWERRather than consistently wanting to remain distant from their donor offspring, donors' expectations and experiences of contact with donor offspring ranged from none to a close personal relationship.WHAT IS KNOWN ALREADYDonor conception is part of assisted reproduction in many countries, but little is known about its continuing influence on gamete donors' lives.STUDY DESIGN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 30 publications
0
29
0
3
Order By: Relevance
“…Previous studies of donors in various locations have found them to be invested in 'passing on' their genes to worthy mothers, regardless of their investment in parenting (Riggs and Scholz, 2011), and to have a broad range of willingness and active desire for contact (Kirkman et al, 2014;Speirs, 2007). Research into the parents' of donors who discovered their children had donated gametes reported a wide variety of reactions, ranging from enthusiasm and a desire to meet with the donor offspring to confusion and worry (Beeson et al, 2013).…”
mentioning
confidence: 99%
“…Previous studies of donors in various locations have found them to be invested in 'passing on' their genes to worthy mothers, regardless of their investment in parenting (Riggs and Scholz, 2011), and to have a broad range of willingness and active desire for contact (Kirkman et al, 2014;Speirs, 2007). Research into the parents' of donors who discovered their children had donated gametes reported a wide variety of reactions, ranging from enthusiasm and a desire to meet with the donor offspring to confusion and worry (Beeson et al, 2013).…”
mentioning
confidence: 99%
“…In comparison, as already mentioned, donors have received much less attention. The research that does exist has tended to be quantitative in nature, exploring mainly anonymous donors' motivations for donating, as well as their attitudes towards donor offspring and potential future contact with said offspring (Crawshaw et al 2007, Daniels and Lewis 1996, Daniels et al 2011, Freeman et al 2016, Jadva et al 2011, Kirkman et al 2014, Speirs 2012, Wheatley 2017; for a systematic review, see van den Broeck et al 2013). However, as pointed out by van den Broeck et al (2013), donors have not been regarded as people in their own right.…”
Section: Donating In Context and Researchmentioning
confidence: 99%
“…Many donors have families of their own and some may have chosen not to disclose to their partner or children that they had donated gametes. Some donors fear that their partners and family members will react negatively to this discovery, seeing donation as a form of infidelity or betrayal 5 . Even with the contact preference provisions of the new law, donors may nevertheless experience psychological distress at the mere fact that their children know their identity.…”
Section: The Rights Of Donor Children Versus Those Of Donor Parentsmentioning
confidence: 99%